2006
DOI: 10.1111/j.1744-7410.2006.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the sponge Tethya orphei (Porifera, Demospongiae) with filamentous cyanobacteria

Abstract: Abstract. Specimens of the sponge Tethya orphei, collected in February 2005 on the underside of coral stones on Arì Athol (Maldives), have been processed for histological and ultrastructural investigations. The cortical layer of the sponge was found to be permeated by filamentous cyanobacteria, the trichomes of which measured 45–63 μm on average and were composed of 10–14 cells. The fine organization of the filaments was consistent with their taxonomic identification as Oscillatoria spongeliae. These filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Given that bacteria and archaea are the only organisms able to oxidise ammonium (Francis et al, 2005;You et al, 2009); the significant excretion of nitrite by C. incrustans suggests that this species may harbour micro-organisms that are responsible for the nitrite flux observed (Jiménez & Ribes, 2007). However, it remains to be elucidated if the three species mentioned above are photosynthetic sponges or not, although there are studies that have determined the presence of phototrophic micro-organisms in other sponges (see Gaino et al, 2006;Lemloh et al, 2009;Sipkema & Blanch, 2010). In contrast, H. venustina released nitrate during autumn of the first year, while Strongylacidon sp.…”
Section: Discussionmentioning
confidence: 94%
“…Given that bacteria and archaea are the only organisms able to oxidise ammonium (Francis et al, 2005;You et al, 2009); the significant excretion of nitrite by C. incrustans suggests that this species may harbour micro-organisms that are responsible for the nitrite flux observed (Jiménez & Ribes, 2007). However, it remains to be elucidated if the three species mentioned above are photosynthetic sponges or not, although there are studies that have determined the presence of phototrophic micro-organisms in other sponges (see Gaino et al, 2006;Lemloh et al, 2009;Sipkema & Blanch, 2010). In contrast, H. venustina released nitrate during autumn of the first year, while Strongylacidon sp.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence for vertical transmission of bacteria has been reported for both types (97,116,118,181,362,419,422,431), while asexual reproduction, i.e., budding, could also contribute to symbiont transfer in some species (146). Indeed, gemmules, the asexual buds of freshwater sponges, contain symbiotic zoochlorellae in at least some species (372), while a bud protruding from the surface of the marine sponge Tethya orphei contained a symbiotic cyanobacterium (117).…”
Section: Ecological Aspects: From Single Cells To the Global Scale Esmentioning
confidence: 99%
“…(Corallini and Gaino 2003). Many sponges are symbiotic with fungi (Gaino et al 2014) and photosynthetic organisms such as cyanobacteria (Arillo et al 1993;Burgsdorf et al 2014;Gaino et al 2006), diatoms Cerrano et al 2004a, b), zoochlorellae (Van Trigt 1918), zooxanthellae , and macroalgae (Bergquist and Tizard 1967;Davy et al 2002;Dawson 1953;Rützler 1990;Trautman and Hinde 2001;Trautman et al 2000Trautman et al , 2003Tronchin et al 2006), with possible benefits for both partners. The host may obtain fixed carbon or nitrogen from the symbiont, while algae exploit the host's catabolites, gain protection from grazers and ultraviolet radiation and increase dispersal capacity through fragmentation (Ávila et al 2007;Rützler 1990;Wilkinson and Fay 1979).…”
Section: And Even Caddisfliesmentioning
confidence: 96%
“…Microalgae and cyanobacteria (Brümmer et al 2008;Gaino et al 2006) were found in the inner tissues of several Tethya species, leading to hypothesize that spicules could act as optical fibres, which are able to capture light from the sponge surface and transfer it towards its inner portions (Cattaneo-Vietti et al 1996).…”
Section: And Even Caddisfliesmentioning
confidence: 99%